IMPORT SUBSTITUTION POTENTIAL IN AGRARIAN AND INDUSTRIAL COMPLEX OF THE REGION - V. Balikoyev; Z. Dzakoev; M. Kantemirova (Вестник университета)
In the article the analysis of opportunities of import substitution at the enterprises of agriculture, the overworking and food industry on the example of the Republic Northern Ossetia-Alania is carried out. The main indicators of their activity are investigated, problems are revealed and ways of realization of import substitution are defined.